Deflection monitoring and assessment for a suspension bridge using a connected pipe system: a case study in China. Issue 12 (12th May 2015) - Liu, Yang; Deng, Yang; Cai, C. S.
Summary: This paper discusses the application of a connected pipe system (CPS) to a suspension bridge in China for the purpose of vertical deflection monitoring and assessment. The CPS mainly consists of three main parts: the pressure transmitters to detect the height change of liquid, the pipes to connect the reference point and measurement points, and the liquid to fill the connected pipes. Multiple pressure transmitters, taken as the measurement point, were mounted inside of the girder. A reference transmitter was mounted inside of a tower, taken as a fixed point. To verify the performance and reliability of the CPS, a controlled load test after the completion of the bridge construction and an uncontrolled load test under the actual traffic loading were carried out. The results showed that the CPS exhibited excellent capability in real‐time measurement of vertical deflection of the suspension bridge. With the long‐term deflection data monitored by the CPS, the extreme deflections with respect to vehicle loads were predicted by extreme value analysis. The generalized extreme value distribution was adopted to establish the probability models of the daily maximum and minimum deflection sequences, and then the extreme deflections within the design reference period of 100 years were determined based on the probability models. Comparison of the extreme deflections and the deflection thresholds was carried out. The deflection monitoring and assessment method proposed in this paper have shown high potential of applicability in the practice of health monitoring for long‐span bridges. Copyright © 2015 John Wiley & Sons, Ltd.